The Urgency of a 30 Percent Free Float Regulation to Strengthen Legal Protection for Retail Investors - Wayan Agitha Reliadewi; Komang Satria Wibawa Putra (Program Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam Sultan Agung, 2025)
This study analyzes the urgency of increasing the minimum free-float threshold to 30 percent as a legal instrument to strengthen retail investor protection and improve the quality of Indonesia’s capital market. The current minimum free-float requirement of 7.5 percent, as regulated in Indonesia Stock Exchange Regulation No. I-A, is no longer sufficient to ensure trading liquidity, prevent price manipulation, or protect minority shareholders. Using a normative legal method based on statutory, conceptual, and comparative approaches, this research compares Indonesia’s regulatory framework with practices adopted in several jurisdictions. The United Kingdom sets a minimum free float of 10 percent for domestic companies and 25 percent for non-UK issuers; Malaysia requires at least 15 percent; Hong Kong mandates a 25 percent public float; Japan imposes a 35 percent tradable share ratio for Prime Market listings; and India requires a minimum public shareholding of 25 percent. The findings show that Indonesia’s free-float level remains far below these jurisdictions, making the market more vulnerable to volatility and potential price intervention. The limited shareholding dispersion also weakens regulatory oversight and reduces the likelihood of Indonesian stocks being included in global indices that rely on free-float-adjusted market capitalization. Increasing the free-float requirement to 30 percent has the potential to broaden public ownership, strengthen corporate governance, enhance liquidity, and increase investor confidence. Establishing this requirement at the statutory level is essential to provide legal certainty and to support more effective supervision by the Financial Services Authority (OJK).